Effect Of Enterpreneurial Caracterisrics And Inovation Around Tais Weaving Business Performance In Timor Leste - António da Costa; Endang Eviline Giri; Augusto da Conceição Soares (ABM: International Journal of Administration, Business and Management, 2020)
Small and medium-size businesses (SMEs) have a strategic role in national economic development, and are proven to contribute greatly towards the economic growth and employment opportunity to many local woman and girls particularly in rural and remote areas around the country. The scheme of empowering SMEs with resilience and competitiveness approaches is one of the strategic efforts needed to prioritize the ability of SMEs, based on the application of entrepreneurial and innovation characteristics plan and approach accordingly. This study aims to analyze and describe the effect of entrepreneurial and innovation characteristics around Tais weaving business performance in Timor-Leste. The results showed positive outcome with the influence of entrepreneurship and innovation characteristics, which significantly portraits positive performance of weaving Tais's business in Timor-Leste, the increasing ability to manage their businesses activities and empowering creative innovation abilities within and around their productivity efforts, promising values and achievement outcome in the future. The analysis Determination of (R2), determines the extent to which the independent variable (X) effects of the ups and downs, the dependent variable (Y), then all data calculations and analyses later details the performances using the computer program of "SPSS" (Statistic Product for Service Solution) 21". Keywords: characteristics of entrepreneurship, innovation and business performance